“Himmapan” Symphonic Poem for the trombone ensemble: The Cycle Process - Charoensloong, Thitinun; Thammabutr, Narongrit (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
“Himmapan” Symphonic Poem for the trombone ensemble: The Cycle Process. It was a creative researched to composed a symphonic poem type of music for a trombone. The researcher was inspired to travel in the Himmapan forest. which was a forest in literature and belief in Triphum according to the beliefs of Buddhism and Brahmins–Hinduism (Triphum:2555). It was believed that the Himmapan Forest is a place It was covered with snow all year round, located in the Indian subcontinent. Consisting of 7 sacred ponds, each pond was also home to the creatures that have a cycle of death and birth. The researcher has proposed ideas and content with 3 composing experts, resulting in the creation of songs. “Himmapan” was the structure and concept of the Symphonic Poem song for the trombone band. In the first movement; The Cycle Process: the researcher chooses to use ternary form; an introduction and section A represent the main melody of this movement. Section B was the development of melody and harmony. Finally, the return of section A' combined with the coda of the song. Therefore, the researcher used a quintal harmony and using the C and G pentatonic scales and extended technique for trombones, non-standard glissando to mimic the sounds of Himmapan creatures. When you listen to this song, you will get a taste of the sultry and exotic sound.